2016
DOI: 10.1177/1076029615579098
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Prediction of Central Venous Catheter Related-Thrombosis in Patients With Hematological Malignancies

Abstract: Elevated leukocyte count, high PAI-1, and high FVIII were associated with an increased incidence of symptomatic CVC-related thrombosis. We hope in future that simple, easy to determine laboratory tests that reflect the hemostatic and fibrinolytic activity in combination with clinical parameters may help to identify hematological patients at highest risk of CVC-related thrombosis and help to tailor the management of thromboprophylaxis in hematological patients undergoing CVC placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 37 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Patients who went on to develop thrombosis had higher factor VIII (FVIII) immediately following CVC placement (203 ± 62% vs 166 ± 59%, p = 0.023). [21]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who went on to develop thrombosis had higher factor VIII (FVIII) immediately following CVC placement (203 ± 62% vs 166 ± 59%, p = 0.023). [21]…”
Section: Resultsmentioning
confidence: 99%
“…They reported mean protein S antigen levels of 100% ± 34 in patients with CVC-related thrombosis and 93% ± 29 (p = 0.417) in patients with vs without VTE. [21] Aue et al, previously described, examined median levels of protein S and found no overlap between 5 (of 32) patients with DVT and an additional 5 with low protein S (<55%) and no patients with low protein C (<59%). [20] Auwerda et al studied protein C and S levels in 135 adult patients with untreated multiple myeloma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several adult studies demonstrated the association of elevated TG parameters with the occurrence of the first VTE event (OR = 1.7) and with recurrence of unprovoked VTE (ORs = 1.6‐4.6) . Similarly, FVIII has shown prospective predictive potential in a subset of adults, both in association with CVC and without CVC (adjusted OR = 3), with FVIII levels >200%. None of these studies evaluated the value of combining clinical prediction tools and biomarkers, but several compared the two approaches in the evaluation of at‐risk adults …”
Section: Discussionmentioning
confidence: 99%
“…In critically ill adults, d‐dimer has also been shown to be predictive of DVT . Other proteins, such as thrombin‐antithrombin complex (TAT), prothrombin fragment 1+2 (PF1+2), plasminogen activator inhibitor‐1, and soluble P‐selectin, have been shown to be associated with incident DVT in adults . Except for d‐dimer, none of these has been tested to predict DVT in children …”
Section: Introductionmentioning
confidence: 99%